Rational Parameters Selection Influence to the Adequate Selection Algorithm by Estimating Local Oxide Influence - Andriukaitis, D. (Elektronika ir Elektrotechnika, 2010)
The production process is a sequence of operations in order to obtain the implementation of the elements or integrated structures with the necessary performance characteristics of the very large scale integration. In this case the manufacture of integrated circuits focuses on the area where the integrated element is being formed. It is essential that the area dimensions at the beginning of the technological processes must be kept the same during the whole technological process. Rational parameters are defined of the thermal process simulation, creating the LOCOS, where the t=90 min, T=1100 ºC, SiO2=0,02 μm, Si3N4=0,1 μm (PO2=1 atm) in the three-dimensional integrated structures. Ill. 6, bibl. 5 (in English; summaries in English, Russian and Lithuanian).